2020
DOI: 10.7554/elife.55619
|View full text |Cite
|
Sign up to set email alerts
|

The effect of climate change on yellow fever disease burden in Africa

Abstract: Yellow Fever (YF) is an arbovirus endemic in tropical regions of South America and Africa and it is estimated to cause 78,000 deaths a year in Africa alone. Climate change may have substantial effects on the transmission of YF and we present the first analysis of the potential impact on disease burden. We extend an existing model of YF transmission to account for rainfall and a temperature suitability index and project transmission intensity across the African endemic region in the context of four climate chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 55 publications
(96 reference statements)
1
26
0
2
Order By: Relevance
“…Temperature suitability was calculated as in Gaythorpe et al, 2020 . The form of the temperature suitability index is given by: where the bite rate, extrinsic incubation period, and mosquito mortality, given by , and µ, respectively, are affected by temperature T in the following ways: following ( Mordecai et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature suitability was calculated as in Gaythorpe et al, 2020 . The form of the temperature suitability index is given by: where the bite rate, extrinsic incubation period, and mosquito mortality, given by , and µ, respectively, are affected by temperature T in the following ways: following ( Mordecai et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The subscripts , and m represent the positive rate constant, minimum temperature, and maximum temperature for each thermal response model. These were estimated within a Bayesian framework, and we retain the point estimates shown in Table 2 ( Gaythorpe et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…As temperature is a key determinant of YF transmission, 44–48 , we estimated R 0 MH and R 0 HM using a temperature-dependent model, following Gaythorpe et al . 49 and Mordecai et al . 50 (see Supplementary Materials ).…”
Section: Methodsmentioning
confidence: 93%
“…Documented rises in average temperatures and precipitation patterns are clear indications of global climate change [41]. A recent report by the 'The Intergovernmental Panel on Climate Change' (IPCC) suggested that if current trends continue, the global mean temperatures will likely rise by 1.5°C between 2030 and 2052 [42].…”
Section: Factors Shaping Yfv Transmission Cyclesmentioning
confidence: 99%